Hardening Blueberry Plants to Face Drought and Cold Events by the Application of Fungal Endophytes - Acuña Rodríguez, Ian S.; Ballesteros, Gabriel I.; Atala, Cristian; Gundel, Pedro Emilio; Molina Montenegro, Marco A. (Agronomy)
Harsh environmental conditions derived from current climate change trends are among the main challenges for agricultural production worldwide. In the Mediterranean climatic region of central Chile, sudden occurrence of spring cold temperatures in combination with water shortage for irrigation (drought) constitutes a major limitation to highbush blueberry (Vaccinium corymbosum) plantations, as flowering and fruiting stages are highly sensitive. Hardening crops may be achievable by boosting beneficial interactions of plants with microorganisms. Inoculation with symbiotic fungi isolated from plants adapted to extreme environments could be a good strategy, if they are able to maintain functional roles with non-original hosts. Here, we evaluated the effect of two Antarctic fungal endophytes (AFE), Penicillium rubens and P. bialowienzense, on the tolerance of V. corymbosum plants to cold events in combination with drought under controlled conditions. Inoculated and uninoculated plants were exposed for a month to one event of a cold temperature (2◦C/8 h) per week with or without drought and were evaluated in physiological, biochemical, and molecular variables. A complementary set of plants was kept under the same environmental conditions for two additional months to evaluate survival as well as fruit weight and size. There was an overall positive effect of AFE on plant performance in both environmental conditions. Endophyte-inoculated plants exhibited higher gene expression of the Late Embryogenesis Abundant protein (LEA1), higher photochemical efficiency (Fv/Fm), and low oxidative stress (TBARS) than uninoculated counterparts. On the other hand, plant survival was positively affected by the presence of fungal endophytes. Similarly, fruit diameter and fruit fresh weight were improved by fungal inoculation, being this difference higher under well-watered condition. Inoculating plants with fungal endophytes isolated from extreme environments represents a promising alternative for hardening crops. This is especially ...